(untitled) (West African Journal on Sustainable Development, 2024)
The removal of fuel subsidy in Nigeria on May 29, 2023 is one action that challenges organizations to show their adaptability skills to corporate external environmental forces. A lot of research gaps have also been observed in the removal of the fuel subsidy in the country. The objectives of the study therefore, are to examine the relationship between fuel subsidy removal and green innovation (use of solar panels); and evaluate the level of correlation between fuel subsidy removal and Liquefied Petroleum Gas(LPG) conversion in Owerri-based health facilities. The research employs the survey research design. The study employs the Economic Theory of Subsidies and Welfare for the theoretical framework. A structured questionnaire was the major instrument for data collection. The study uses Cronbach Alpha statistic for obtaining 0.86 as the reliability ratio of the survey instrument. The research commits data analysis to descriptive statistics of mean and standard deviation and it employs correlation analysis for testing hypotheses. The findings show that there is a significant relationship between fuel subsidy removal and green innovation (use of solar panels); and there is significant level of correlation between fuel subsidy removal and Liquefied Petroleum Gas(LPG) conversion in health facilities at Owerri. The study concludes that fuel subsidy removal is a correlate of sustainable organizational agility in Owerri-based health facilities and organizations that desire sustainability and agility embrace divergent thinking always. The study recommends that the management of the various health facilities in Owerri should not see the removal of fuel subsidy as a punishment or anti-economic policy but an opportunity to be innovative with renewable and sustainable energy options. Also, management of health facilities should leverage on the fuel subsidy removal to create energy-based partnerships for seamless growth and stability in medical operations.